The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1177/003776867201900308
|View full text |Cite
|
Sign up to set email alerts
|

Parental Images and Representations of God

Abstract: Depuis une dizaine d'années, le « Centre de Psychologie de la Religion » de Louvain s'est attaché à l'étude empirique des figures parentales en tant que médiatrices de la repré sentation de Dieu chez les sujets contemporains. L'instrument élaboré consiste en une liste de 36 qualités, 18 qualités ex pressément paternelles, c'est-à-dire attribuées généralement à la figure du Père, et 18 qualités maternelles, que les sujets doivent associer d'abord aux deux images parentales et ensuite à la figure de Dieu. Et ce,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Third, Vergote et al (1969) found that in their American samples, both males and females emphasized the paternal image of God rather than the maternal image and that this tendency was even stronger in males than females. The parental image of God was also emphasized by both boys and girls within the two Asian communities reported by Vergote and Aubert (1973). These findings may suggest greater paternal influence on the religious development of both sons and daughters.…”
mentioning
confidence: 78%
“…Third, Vergote et al (1969) found that in their American samples, both males and females emphasized the paternal image of God rather than the maternal image and that this tendency was even stronger in males than females. The parental image of God was also emphasized by both boys and girls within the two Asian communities reported by Vergote and Aubert (1973). These findings may suggest greater paternal influence on the religious development of both sons and daughters.…”
mentioning
confidence: 78%
“…First, Vergote et al (1969) found that in their American samples, both males and females emphasised the paternal image of God rather than the maternal image and that this strand was even stronger in males than in females. The paternal image of God was also emphasised by both boys and girls within the two Asian communities reported by Vergote and Aubert (1973) and by the hospital patients and members of an adult Sunday school in the U.S.A. study reported by Justice and Lambert (1986). Similarly Gibson (1994) demonstrated that both boys and girls are much more likely to believe that God is like a father than to believe that God is like a mother.…”
Section: Depth Psychologymentioning
confidence: 97%
“…Obviously in the past there was no lack of in-depth studies on spontaneous, individual prayer (Bertrand 1993;Vergote and Aubert 1972; which, however, where limited to analysing the role of this practice within the dynamics of church religions or institutionalized forms of religious expression, so that prayer was often considered a second-rate indicator of religiosity because of the importance assigned to other religious dimensions such as beliefs and participation in community rituals.…”
Section: Prayer In Advanced Modernitymentioning
confidence: 99%